Substrate Doping Effect and Unusually Large Angle van Hove Singularity Evolution in Twisted Bi‐ and Multilayer Graphene. Issue 27 (8th May 2017) - Peng, Han; Schröter, Niels B. M.; Yin, Jianbo; Wang, Huan; Chung, Ting‐Fung; Yang, Haifeng; Ekahana, Sandy; Liu, Zhongkai; Jiang, Juan; Yang, Lexian; Zhang, Teng; Chen, Cheng; et al.
Abstract : Graphene has demonstrated great potential in new‐generation electronic applications due to its unique electronic properties such as large carrier Fermi velocity, ultrahigh carrier mobility, and high material stability. Interestingly, the electronic structures can be further engineered in multilayer graphene by the introduction of a twist angle between different layers to create van Hove singularities (vHSs) at adjustable binding energy. In this work, using angle‐resolved photoemission spectroscopy with sub‐micrometer spatial resolution, the band structures and their evolution are systematically studied with twist angle in bilayer and trilayer graphene sheets. A doping effect is directly observed in graphene multilayer system as well as vHSs in bilayer graphene over a wide range of twist angles (from 5° to 31°) with wide tunable energy range over 2 eV. In addition, the formation of multiple vHSs (at different binding energies) is also observed in trilayer graphene. The large tuning range of vHS binding energy in twisted multilayer graphene provides a promising material base for optoelectrical applications with broadband wavelength selectivity from the infrared to the ultraviolet regime, as demonstrated by an example application of wavelength selective photodetector. Abstract : Tuning the twist angle in twisted bilayer graphene provides an intriguing route to engineer graphene's band structure for optoelectronic applications. In this work, interlayer coupling over a wide twist angle range (5°–31°) is reported, which leads to van Hove singularities with energy separation up to 2 eV. Furthermore, the doping of multilayer graphene by copper substrate is investigated in detail.